UPAYA PENURUNAN KECACINGAN ANAK SD DI DESA SUNGAI KUNYIT HULU MENGGUNAKAN VIDEO ANIMASI DAN PRAKTEK MENCUCI TANGAN - Tilawaty Aprina; Fath Dwisari; Nurli Arnida; Ainun Sa'adah (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2023)
More than 1.5 billion people in the world experience helminthiasis and are found mostly in tropical and subtropical regions, where the highest incidence is in China, Latin America, sub-Saharan Africa and Southeast Asia, one of which is Indonesia. Worms are often associated with sanitation, education, socio-economic factors and daily behavior. As much as 12% of the total morbidity of students aged 5-14 years in developing countries is infected with worms, and at that age is the school period and is a group that is vulnerable to disease transmission. The prevalence of intestinal worms in Indonesia varies from 2.5% to 65%. This figure increases if the prevalence of helminthiasis is calculated in school-age children, to 80%. According to observations made, children in Sungai Kunyit Hulu Village, Mempawah Regency, where after observations in October 2022, 26 out of 45 children were positive for helminthiasis. Most elementary school children with poor socio-economic backgrounds have an unhealthy living environment. Hygiene issues are often neglected, especially hand hygiene issues. This activity aims to increase children's and parents' knowledge about the dangers of helminthiasis and their prevention through proper and proper hand washing. Counseling materials in the form of animated videos, SAP, leaflets, and power points. In addition, the organizing team also prepared equipment to be used for hand washing practice activities and a set of tools for helminth staining examination. Information dissemination on helminthiasis and good and correct hand washing practices are expected to increase prevention and reduce helminthiasis in the Sungai Kunyit Hulu Village area.